2021
DOI: 10.2147/cia.s337069
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Adverse Events Among Chronic Total Occlusion Patients Undergoing Successful Percutaneous Coronary Intervention and Medical Therapy

Abstract: Objective Limited data are available on the predictors of major adverse cardiac events (MACE) after a successful coronary chronic total occlusion (CTO) percutaneous coronary intervention (PCI) and medical therapy. This study aimed to identify predictors of MACE in CTO patients undergoing successful recanalization and medical therapy. Methods A total of 2015 patients with CTOs were enrolled. About 718 patients underwent successful CTO recanalization, and 1297 patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Additionally, when combined endpoints including repeat revascularizations and re-hospitalizations are adopted, previous study showed different outcomes for PCI vs CABG for patients with complex coronary disease. 23 Thus, we considered the strategy of revascularization as a relevant variable to be included within the multivariable adjustment to reduce the impact of confounding factors, 24 and we found PCI (compared with CABG) was independently associated with a higher MACCE rate in these patients, possibly due to the incomplete revascularization of PCI, which was consistent with prior study. 23 Therefore, with the latest refinement equipment and techniques, in treating patients with TVD, revascularization should be highly preferred as the treatment option and should not be limited by gender.…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, when combined endpoints including repeat revascularizations and re-hospitalizations are adopted, previous study showed different outcomes for PCI vs CABG for patients with complex coronary disease. 23 Thus, we considered the strategy of revascularization as a relevant variable to be included within the multivariable adjustment to reduce the impact of confounding factors, 24 and we found PCI (compared with CABG) was independently associated with a higher MACCE rate in these patients, possibly due to the incomplete revascularization of PCI, which was consistent with prior study. 23 Therefore, with the latest refinement equipment and techniques, in treating patients with TVD, revascularization should be highly preferred as the treatment option and should not be limited by gender.…”
Section: Discussionsupporting
confidence: 74%
“…This was consistent with the findings of Iglesias and his colleagues ( 85 , 86 ), who found that higher-risk patients were highly likely to benefit from the “treatment-risk paradox”, which is a common procedure in PCI. Since patients with prior CABG represent a significant proportion (37%) of those undergoing CTO PCI ( 87 , 88 ), these findings indicate that this procedure has more clinical benefits in patients with prior compared to those in the non-CABG group. Indeed, those patients with prior CABG are older, with many comorbidities, extensive and complex coronary lesions, and they are more likely to present concurrent cardiovascular risk factors.…”
Section: Future Perspectivesmentioning
confidence: 98%